War and Faith the Catholic Church in Slovenia, 1914-1918. - Bobic, Pavlina; Bobi, Pavlina; Lang, Prof Bernhard (Leiden : BRILL, 2012)
Drawing on the themes of religious rhetoric, embedded in social and political contexts, this study offers new insights into the manners in which the Catholic Church helped mould the Slovenians' responses to WWI and reconsiders the reasons for the clergy's political actions amid tensions, which resulted in the Habsburg empire's collapse.
Acknowledgements; List of Illustrations; List of Abbreviations; Note on Pronunciation; Maps; Introduction; Chapter One The Catholic Church Between the Nation and State in July and August 1914; Chapter Two Italy "ante portas"; Chapter Three From Holy to Bloody War; Chapter Four Guardians of the True Faith; Chapter Five "Austria Nova" or "The Compass of Austria is Pointed Southwards"; Chapter Six "Lift Up Your Heads, for Your Redemption is Near!": The Dawn of Yugoslavia; Conclusion; Bibliography; Index.
Description based on print version record.
Keywords: Austria -- History -- 1867-1918.; Catholic Church -- Political activity -- Slovenia -- History -- 20th century; Catholic Church -- Slovenia -- Clergy -- History -- 20th century; Catholic Church -- Slovenia -- History -- 20th century; Church and state -- Slovenia -- History -- 20th century; Habsburg, House of; Nationalism -- Slovenia -- History -- 20th century; World War, 1914-1918 -- Austria; World War, 1914-1918 -- Religious aspects -- Catholic Church; Religion; Habsburg, House of; Catholic Church -- Political activity -- Slovenia -- History -- 20th century; Catholic Church -- Slovenia -- Clergy -- History -- 20th century; World War, 1914-1918 -- Religious aspects -- Catholic Church; Church and state -- Slovenia -- History -- 20th century; Nationalism -- Slovenia -- History -- 20th century; Austria -- History -- 1867-1918.; RELIGION / Christianity / Catholic; Electronic books